FACTORS AFFECTING MALE AND FEMALE INDONESIAN EFL STUDENTS’ WRITING ANXIETY - Salikin, Hairus (Indonesian Journal of Applied Linguistics, 2019)
This study is aimed at investigating the writing anxiety levels of foreign language learners and factors affecting the foreign language writing anxiety levels on the learners based on the gender variable. It applies close-ended questionnaires as instruments to collect the data, adopted from Cheng (2004) about Second Language Writing Anxiety Inventory (SLWAI), and Causes of Writing Anxiety Inventory (CWAI) questionnaire adopted from Younas (2014). The results of the study show that Indonesian English learners suffered a mediocre level of English writing anxiety, especially cognitive anxiety as preference. In relation to gender, female students tend to have significantly higher anxiety level than male in terms of writing English compositions. The study reports that both male and female learners suffered from anxiety due to lack of linguistic competence.